Webs and Hierarchies: Individuation in Munro and Hemingway - Arbing, Susan (My University, 1992)
This study examines the reproduction of universal gender differences through the construction of masculine and feminine identities, the development of unconscious personality traits in an environment where women mother, and the role of external influences such as sex-role ideology and socialization outside the home using feminist developmental theory and two texts, Hemingway's The Nick Adams Stories and Munro's Lives of Girls and Women. Chapter 1 establishes masculine and feminine characteristics of gender identity through a close examination of Dr. Henry Adams and Ida Jordan, the parents of the two protagonists. Chapter 2 looks at the development of unconscious gender traits through the development of Nick Adams and Del Jordan. The role of the mother-child relationship and the father-child relationship in the creation of personality will also be examined. Chapter 3 examines the result of this process, the mature Nick Adams and Del Jordan, in their respective environments outside the home, paying particular attention to the protagonists' responses to social expectations of role behaviour. In conclusion, this study contends that gender and personality traits are reproduced through social organization and socialization and may be reinforced through literature.
Keywords: Munro; Hemingway